A gallery walk na educação básica: um olhar para as produções científicas do período de 2010 a 2020 - Correia, Thaís Fernanda de Aquino (Universidade Federal de São Carlos, 2021)
The present research had as investigative scope an active teaching strategy called Gallery Walk when inserted in the teaching scope of Mathematics and Natural Sciences. Gallery Walk is similar to an art gallery, in which visitors try to understand what the artist expressed through his artistic exhibition. During the activity permeated by this teaching strategy, students can move around the room and talk to their groups with the intention of observing images, posters or even their own work. Along this route, they can contribute with comments, share ideas and request clarification from colleagues about the doubts that have arisen along the way. Furthermore, it is possible that problems-issues or tasks may be introduced to be jointly solved, in order to encourage collaborative work and the active engagement of students. In this sense, this research was guided by the following question: How has Gallery Walk been used in Basic Education, according to scientific productions for the period 2010 to 2020? This research can be characterized as qualitative, exploratory and bibliographical. To answer the research question, a survey of scientific publications was carried out in four online academic search platforms. From a total of 60 items, ten productions were selected and analyzed, as some of them were present in more than one platform. In this way, it was possible to identify the analysis categories for each of the areas. In relation to the area of Mathematics, three categories of flexibility were constructed, namely: broad, intermediate and restricted. And, for Science of Nature, the category entitled walk in the gallery was created. The results point to the positive effects of inserting this active teaching strategy in teaching and learning contexts, especially for the two areas mentioned, in addition to demonstrating the gaps in academic productions about Gallery Walk in Brazil and abroad. Therefore, this research recommends the production of new research on the theme Gallery Walk in other online platforms and filters, as well as works in different areas of knowledge.
The gallery walk in basic education: a look at scientific productions from 2010 to 2020.
Keywords: Estratégia de ensino; Educação básica; Ensino de Matemática e de Ciências da Natureza; Gallery walk; Teaching strategy; Basic education; Teaching of Mathematics and Natural Sciences; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM